Age-dependent alteration of TGF-β signalling in osteoarthritis - van der Kraan, Peter M. (Springer-Verlag, 2011)
Osteoarthritis (OA) is a disease of articular cartilage, with aging as the main risk factor. In OA, changes in chondrocytes lead to the autolytic destruction of cartilage. Transforming growth factor-β has recently been demonstrated to signal not only via activin receptor-like kinase 5 (ALK5)-induced Smad2/3 phosphorylation, but also via ALK1-induced Smad1/5/8 phosphorylation in articular cartilage. In aging cartilage and experimental OA, the ratio ALK1/ALK5 has been found to be increased, and the expression of ALK1 is correlated with matrix metalloproteinase-13 expression. The age-dependent shift towards Smad1/5/8 signalling might trigger the differentiation of articular chondrocytes with an autolytic phenotype.